THE ANALYSIS ON RACISM IN 12 YEARS A SLAVE MOVIE - Anriadi; Fathu Rahman; Amir Pattu (Universitas Hasanuddin, 2022)
This study discusses a practice of racism carried out by the upper class to the lower class. Racism is behavioral differences and inequalities based on a person's skin color, race, ethnicity, and origin that limit or violate a person's rights and freedoms. Racism is often interpreted as the view that humans can be divided into separate groups based on biological characteristics called